Biochemical basis of apple leaf resistance to Erwinia amylovora infection - Viljevac Vuletić, Marija (Array, 2009)
Summary: Erwinia amylovora is the most frequently found necrogenic bacterium on apple (Malus domestica Borkh.) trees, which causes progressive necrosis and blight of host plants. Rapid spread of bacteria through the host tissue can lead to the loss of entire trees in one growing season. In this work, the aim is to investigate long-lasting biochemical responses in leaves of two apple cultivars (Enterprise and Golden delicious). Several histochemical (polyphenols, suberin and callose) and biochemical parameters (total polyphenols, superoxide dismutase – SOD, ascorbate peroxidase – APX and guaiacol peroxidase – GPOD) were screened 60 days after Erwinia inoculation in order to find their potential correlation with plant resistance mechanisms to the pathogen attack. Differential susceptibility to the pathogen attack observed between the investigated cultivars was in accordance with previous studies that characterized Enterprise as less susceptible and Golden delicious as more susceptible cultivar. Infected leaves of Golden delicious expressed symptoms seen as large brown areas at the abaxial side mostly placed at the leaf margin and necrosis also found peripherally, while damage in Enterprise leaves was observed as small brown spots and sporadic leaf edge necrosis. Increased SOD and GPOD activities combined with decreased polyphenol content as well as wide cuticle suberization in cultivar Enterprise should be considered as reliable biochemical parameters characterizing its ability to develop certain resistance to the pathogen infection. Furthermore, the absence of callose deposition in leaves of Enterprise confirmed our findings that thick suberized cuticle is likely the main defense mechanism that enables long-term efficient protection of apple leaves against biotic stress caused by Erwinia attack